(untitled) (Research, Society and Development, 2021)
The coronavirus pandemic caused several changes in the population’s life, causing psychological consequences that can influence oral health, especially oral diseases that have psycho-emotional factors as their etiology. Objective: perform a literature review about the influence of the COVID-19 pandemic on psychological aspects and its relationship with bruxism and Temporomandibular Disorder (TMD). Methodology: this is a qualitative bibliographic review in which data collection was carried out on the LILACS, BVS, SciELO and PubMed platforms using the descriptors: COVID-19, Oral Health, Psychology, Anxiety, Depression, Bruxism, Temporomandibular Disorders, in English and Portuguese, including articles that addressed the association between psychosocial aspects related to the pandemic by COVID-19 and its connection with bruxism and TMD, in addition to articles that correlated TMD and psychological aspects or that dealt with the pandemic by COVID-19 and its connection with psychological aspects. Results: 19 articles were selected and these showed a relationship between stress, anxiety and depression with bruxism and TMD, with women being the most affected. Conclusion: the COVID-19 pandemic increased levels of stress, anxiety and depression, as well as the incidence and severity of painful symptoms of bruxism and TMD.